Adapting taxation for the digital Economy in Singapore - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2021)
The advent of the digital economy has had profound implications for taxation. Tax systems have been forced to adapt as they become increasingly unsuited for the realities of modern commerce. While Singapore has largely followed international developments, particularly in the area of international taxation, it has often made numerous innovative policy decisions in line with its national interests. The various policy decisions which Singapore has made on taxing the digital economy span both international and domestic tax. In the area of domestic tax, the examples have been further divided by subject matter, like e-commerce, digital tokens, automation, and electronic instruments. Other jurisdictions will face similar choices when considering how to adapt their domestic tax systems for the digital economy, and the tax policy decisions made by a small, highly-open economy such as Singapore may provide insights to jurisdictions seeking to adapt their tax systems for the digital economy.